1995
DOI: 10.1093/infdis/171.6.1632
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Toxicity of Two Doses of Trimethoprim-Sulfamethoxazole as Primary Prophylaxis against Pneumocystis carinii Pneumonia in Patients with Human Immunodeficiency Virus

Abstract: The efficacy and toxicity of trimethoprim-sulfamethoxazole (TMP-SMZ) as primary prophylaxis against Pneumocystis carinii pneumonia (PCP) for patients with human immunodeficiency virus (HIV) infection was assessed by comparing the effects of two dosages (480 or 960 mg once a day) of the drug. The multicenter trial involved 260 HIV-infected patients with CD4 cell counts < 0.2 x 10(9)/L and no history of PCP. Patients were randomly assigned to the treatment groups. After a median follow-up of 376 days (range, 1-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 8 publications
0
28
0
1
Order By: Relevance
“…Prophylaxis with trimethoprim-sulfamethoxazole also appears to protect against toxoplasmic encephalitis, but the optimal dose is unknown and the assessments of efficacy have been based only on a retrospective analysis [24], observational data [34,35], or results of controlled trials that did not primarily target prophylaxis for toxoplasmic encephalitis and therefore yielded small numbers of events [5,6,31,[36][37][38]. While none of these trials revealed a significant protective effect on an intent-to-treat basis, toxoplasmic encephalitis in fact rarely occurred during treatment with trimethoprim-sulfamethoxazole.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylaxis with trimethoprim-sulfamethoxazole also appears to protect against toxoplasmic encephalitis, but the optimal dose is unknown and the assessments of efficacy have been based only on a retrospective analysis [24], observational data [34,35], or results of controlled trials that did not primarily target prophylaxis for toxoplasmic encephalitis and therefore yielded small numbers of events [5,6,31,[36][37][38]. While none of these trials revealed a significant protective effect on an intent-to-treat basis, toxoplasmic encephalitis in fact rarely occurred during treatment with trimethoprim-sulfamethoxazole.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of low-and high-dose regimens (single-or doublestrength TMP-SMZ tablets) for prophylaxis in patients with AIDS suggest no mortality advantage with the higher dose (12% incidence vs. 15% in the lower-dose group) and earlier occurrence of toxicity in the high-dose group [74,81]. Although no Pneumocystis infection was observed in compliant individuals in either group at 1 year of treatment, 63 of 156 patients dropped out because of toxicity.…”
Section: Specific Agentsmentioning
confidence: 99%
“…About one-quarter of HIV-infected patients experience adverse reactions to cotrimoxazole (especially cutaneous intolerance), often leading to withdrawal of treatment (11). The mechanisms underlying these adverse reactions are unclear [toxic (12)(13)(14) and:or immunologic (15)].…”
Section: Introductionmentioning
confidence: 99%